PELAKSANAAN PRINSIP AI-BAY’ BITHAMAN AJIL DALAM PENGGUNAAN KAD KREDIT ISLAM: SUATU KAJIAN DI ARAB-MALAYSIAN BANK BERHAD - Borhan, Joni Tamkin (Jurnal Syariah, 2019)
This article will discuss the doctrine of ai-bay ' bithaman ajil in Islamic Commercial Law as have been developed by Fuqaha' and Muslim Economists in their works and its application in the usage of Islamic credit card as offered by Arab-Malaysian Bank Berhad.